Designing Organizational Development Framework for CV Putri Intan Kencana (Jernip Kencana) - Rahmatullah Karnawidjaya (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to develop an organizational development framework to support succession readiness in a family owned small and medium enterprise, using Jernip Kencana as a case study. A qualitative approach was employed through semi structured interviews, non participant observation, and document analysis. The data were analyzed using thematic analysis guided by Greiner’s Growth Model, the Three Circle Model, and Leavitt’s Diamond Model. The findings indicate that Jernip Kencana is experiencing a crisis of leadership characterized by strong founder dependency, informal operational processes, and limited organizational autonomy. A conflict between family oriented socioemotional priorities and business efficiency creates resistance to professionalization, while misalignment across task, structure, people, and technology variables further weakens succession readiness. This study proposes a culturally adaptive organizational development framework that emphasizes value alignment, gradual delegation of authority, and institutionalization of critical knowledge to ensure business continuity while preserving the company’s social mission.